Cu-II-exchanged montmorillonite K10 clay-catalyzed direct carboxylation of terminal alkynes with carbon dioxide - Aher, Ravindra D.; Gade, Madhuri H.; Reddy, R. Santhosh; Sudalai, Arumugam (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
A new, simple and straight-forward protocol for direct carboxylation of terminal alkynes has been developed using Cu-II-montmorillonite K10 clay as a heterogeneous catalyst and CO2 as the C1 carbon feedstock. Also coupling of terminal alkynes with CO2 (1 atm) in the presence of alkyl halides has been achieved under the same reaction conditions, thereby providing access to a variety of functionalized alkyl-2-alkynoates in high yields.
Keywords: Alkyl esters; Alkyne C-H activation; Carbon dioxide activation; Carboxylation; Catalysts; Montmorillonite clays

One-pot synthesis of cyclic carbonates from aldehydes, sulfur ylide, and CO2 - Aher, Ravindra D.; Kumar, B. Senthil; Sudalai, Arumugam (Synlett, 2014)
Treatment of aldehydes with sulfur ylide (CH2=SOMe2 or CH2=SMe2), in the presence of CO2 (1 atm) bubbled sequentially under mild conditions, produces cyclic carbonates in preparative yields. Sodium iodide formed in situ promotes the reaction between epoxide as intermediate and CO2 at ambient conditions, thus constituting a powerful metal-free synthesis of organic cyclic carbonates directly from aldehydes.
Keywords: Carbon dioxide; cyclic carbonates; cyclization; epoxides; Insertion

Organocatalytic [4+1]-annulation approach for the synthesis of densely functionalized pyrazolidine carboxylates - Lalwani, Komal G.; Aher, Ravindra D.; Sudalai, Arumugam (RSC Advances, 2015)
A novel one-pot [4+1]-annulation process for the asymmetric synthesis of densely functionalized pyrazolidine carboxylates is described. The in situ generated gamma-hydrazino-alpha,beta-unsaturated ester obtained via proline catalysis acts as a four-atom component, and Corey's sulfur ylide or ethyl bromoacetate acts as a one-atom carbon source to construct pyrazolidine carboxylate units in a highly enantio- and diastereoselective fashion.

Proline-catalyzed sequential syn-mannich and [4+1]-annulation cascade reactions to form densely functionalized pyrrolidines - Aher, Ravindra D.; Kumar, B. Senthil; Sudalai, Arumugam (Journal of Organic Chemistry, 2015)
A highly efficient one-pot [4 + 1]-annulation process for the asymmetric synthesis of densely functionalized pyrrolidine derivatives is described. The in situ generated syn-Mannich adduct obtained via proline catalysis acts as a four-atom component, and Coreys sulfur ylide or ethyl bromoacetate acts as a one-atom carbon source to construct pyrrolidine units in a highly enantio- and diastereoselective manner.

Proline catalyzed enantioselective synthesis of (2S,3S)-3-hydroxypipecolic acid and formal synthesis of (+)-swainsonine - Aher, Ravindra D.; Sudalai, Arumugam (Tetrahedron Letters, 2016)
A short enantioselective synthesis of (2S,3S)-3-hydroxypipecolic acid (overall yield: 18.8%; 96% ee) and formal synthesis of (+)-swainsonine (overall yield: 13.6%; 96% ee) have been described starting from commercially available acrolein. The synthetic strategy involves a high enantioselective L-proline catalyzed sequential c-amination and diastereoselective (dr > 99:1) Barbier allylation of aldehyde in one-pot as the key reaction. (C) 2016 Elsevier Ltd. All rights reserved.

Diastereoselective synthesis of chiral 2,3-disubstituted lndolines via formal [3+2]-cycloaddition of arynes with gamma-amino-alpha,beta-unsaturated esters - Aher, Ravindra D.; Suryavanshi, Gurunath M.; Sudalai, Arumugam (Journal of Organic Chemistry, 2017)
A one step formal [3+2]-annulation protocol for the synthesis of 2,3-disubstituted indolines is described. The in situ generated aryne acts as a two-atom component, and gamma-amino-alpha,beta-unsaturated esters acting as a three-atom component to construct indoline units in a highly regio- and diastereoselective manner with yields ranging from 63 to 80%.